REduced‐Carbohydrate intervention for managing Obesity and Reduction of gestational Diabetes (RECORD): A randomized controlled feasibility trial - Michalopoulou, Moscho; Jebb, Susan A.; MacKillop, Lucy H.; Dyson, Pamela; Hirst, Jane E.; Zhu, Sufen; Wire, Amy; Astbury, Nerys M. (Diabetes, obesity & metabolism, 2024)
Aim To test the feasibility and acceptability of a reduced‐carbohydrate dietary program, intended to reduce the risk of gestational diabetes. Materials and Methods Fifty‐one pregnant women at <20 weeks' gestation, with body mass index ≥30 kg/m2, and a normal baseline oral glucose tolerance test (OGTT), were randomized 2:1 to an intervention or control group and followed‐up until delivery. The dietary intervention aimed at providing 130–150 g carbohydrate/day. Feasibility outcomes assessed at 24–28 weeks' gestation, included adoption of the reduced‐carbohydrate diet by the intervention group, and retention of all participants, assessed by completion of a second OGTT. Changes in glycemia, weight gain and dietary intake, and the maternal and neonatal outcomes were also assessed. Participants were interviewed about their experience of the intervention and the study. Results Forty‐nine of 51 participants attended the follow‐up OGTT, a retention rate of 96% (95% confidence interval [CI] 86.8%–98.9%). In the intervention group, carbohydrate intake at follow‐up was 190.4 (95% CI 162.5–215.6) g/day, a reduction of −24.6 (95% CI −51.5–2.4) g/day from baseline. Potentially favourable effects of the intervention on glucose control, weight gain and blood pressure were observed, but the study was not powered to detect significant differences in these. Participants found the intervention acceptable, and were content with the study processes, but some reported barriers to sustained adherence, mainly pertaining to competing priorities. Conclusions Retention was high, suggesting the study processes are feasible, but the carbohydrate reduction in the intervention group was small, and did not meet progression criteria, limiting the likelihood of achieving the desired goal to prevent gestational diabetes. Trial registration number: ISRCTN16235884.